2007
DOI: 10.1093/jxb/ern029
|View full text |Cite
|
Sign up to set email alerts
|

Quantum yield variation across the three pathways of photosynthesis: not yet out of the dark

Abstract: The convergent quantum yield hypothesis (CQY) assumes that thermodynamics and natural selection jointly limit variation in the maximum energetic efficiency of photosynthesis in low light under otherwise specified conditions (e.g. temperature and CO(2) concentration). A literature survey of photosynthetic quantum yield (phi) studies in terrestrial plants from C(3), C(4), and CAM photosynthetic types was conducted to test the CQY hypothesis. Broad variation in phi values from C(3) plants could partially be expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
2
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(94 citation statements)
references
References 77 publications
7
74
2
4
Order By: Relevance
“…Quantum efficiency was set at 0.10 for NDT. These values are still within the range reported in Skillman (2008). An example of the changes is shown in the Supplement, Fig.…”
Section: Radiation (Experiments 4)supporting
confidence: 83%
“…Quantum efficiency was set at 0.10 for NDT. These values are still within the range reported in Skillman (2008). An example of the changes is shown in the Supplement, Fig.…”
Section: Radiation (Experiments 4)supporting
confidence: 83%
“…Th e parameter estimates regarding α were similar to those reported by Peek et al (2002). It was shown that the quantum effi ciency is an intrinsic characteristic, and its upper ceiling in C 3 plants is set fi rmly by physiochemical limitations (Skillman 2008). Under steady-state and non-stressed conditions, quantum yield is generally regarded as constant (Ehleringer, Bjorkman 1977;Oberhuber et al 1993).…”
Section: Discussionsupporting
confidence: 73%
“…This suggests there is strong selection for plants to produce leaves that are as efficient as possible in capturing solar energy in carbohydrates. Interestingly, the maximum realized QY, measured under ambient CO 2 and O 2 concentrations, always falls well below the maximum potential QY determined in the lab under optimal, albeit artificial, controlled CO 2 and O 2 concentrations (Skillman, 2008). This 'real world' inefficiency is largely due to energy losses associated with photorespiration (discussed below).…”
Section: Wwwintechopencommentioning
confidence: 77%